PEMBUATAN DAN KARAKTERISASI ARANG AKTIF DARI BATANG LIMBAH TANAMAN GUMITIR DENGAN AKTIVATOR ZnCl2 - E. Sahara; D. E. Permatasaari; I W. Suarsa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
The agricultural waste of gumitir plants stem can be used as an ingredient in producing an activated carbon. Some researchers have reported that the additions of phosphoric acid and NaOH as chemical activators have resulted in an activated carbon that met the SNI (Indonesian National Standard) 06-3730-1995 about technical activated carbon. The purpose of this study was to produce and characterize the activated carbon from the stem of gumitir plants carbonized at 300oC for 90 minutes with the use of ZnCl2 as the activator. The activation was carried out by adding ZnCl2 to an amount of carbon in various mole ratios. The characteristics of the activated carbon obtained were compared to the SNI. It was evident that the addition of 0.1 mole of ZnCl2 to 1 gram of the carbon produced an activated carbon that met the SNI standard, namely, water content of 5.00%, as content of 8.33%, volatile content of 950oC of heating of 7.36%, carbon content of 79,30%, iodine absorption capacity of 788.1271 mg/g, and methylene blue absorption capacity of 260.7917 mg/g. The surface area and surfae acidity of this carbon was of 677,6270 mg2/g and 0.3396 mmol/g, respectively. The functional group analysis of this activated carbon showed the presence of O-H, COOH, C-O aldehyde, alkaline C-C and C-H groups.